2020
DOI: 10.1039/d0lc00767f
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and rapid 3D printing of microfluidic devices using wavelength selection on a DLP printer

Abstract: The use of microfluidics on synchrotron X-ray beamlines represents an advanced sample preparation and delivery platform for state-of-the-art X-ray characterization of micro-samples. The recent developments of 3D printing technologies have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 54 publications
0
60
0
Order By: Relevance
“…Nordin et al [154] have described a DLP-SLA printer with a custom resin, which has achieved impressive flow channel cross sections with a resolution of 18 × 20 µm. It has been shown that for DLP, better control over the resin polymerisation and quality of the microfluidic devices can be improved by reducing the penetration depth of the UV LED (Light Emitting Diode) light through a combination of wavelength selection and choice of absorber and photo-initiator materials and achieve 37 × 37 µm 2 pixel resolution at a printed layer thickness of 25 µm with a modified desktop printer at 385 nm wavelength [155].…”
Section: D Printingmentioning
confidence: 99%
“…Nordin et al [154] have described a DLP-SLA printer with a custom resin, which has achieved impressive flow channel cross sections with a resolution of 18 × 20 µm. It has been shown that for DLP, better control over the resin polymerisation and quality of the microfluidic devices can be improved by reducing the penetration depth of the UV LED (Light Emitting Diode) light through a combination of wavelength selection and choice of absorber and photo-initiator materials and achieve 37 × 37 µm 2 pixel resolution at a printed layer thickness of 25 µm with a modified desktop printer at 385 nm wavelength [155].…”
Section: D Printingmentioning
confidence: 99%
“…Purely 3D printed chips with the smallest feature sizes require custom 3D printers and resins. The smallest feature sizes are achieved using microstereolithography, 11 modied 3D printers and resins, 24 and high-end or custom 3D printers. 14,16,25,26 Channel sizes down to 18 Â 20 mm have been reported with custom setups.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, microfluidics chips have been fabricated using a custom-made photopolymer printer based on acrylate PDMS, with an aim to improve the method for fabricating PDMS microfluidics devices with reduced time and cost [232]. With efforts made to produce 3D-printed devices with the exact accuracy using the fabrication technique, Peter et al discovered that a reduction in the penetration depth of UV-LED light (through wavelength selection) in combination with the chosen photoinitiator and absorber materials helped achieve channel dimensions as low as 100 μm using a DLP printer [233]. They also reported that it is possible to have absolute control over the resin polymerization.…”
Section: Prospectsmentioning
confidence: 99%